Debaters Perspective toward the Use of Autonomous Learning - Merbawani, Gigih Widy (Department of English Language Education, UIN Sunan Ampel Surabaya, 2022)
Research on the debatable topic of learning autonomy from the perspectives of the debaters is not quite new, however, further discussion is done by seeking the educational implications of autonomous learning used. Therefore, this study investigates the cases of three active debaters under the learning community in students' activity at University. The findings have focused more on how they subjectively position themselves during the learning process of becoming a good debater in the debating Community. First, they agree that the existence of mentors has created a significant difference in the growth and betterment of debater in the learning community. Second, assessment has a huge role to become the extrinsic exposure, the evaluative measurement, as well as raising up learning motivation. Third, during the learning process of becoming a good debater, autonomy can be seen as either individualistic or not depends on each individual to positioned the urge of learning.